Twenty-five best plays of the modern American theatre Early series - Gassner, John 1903-1967 (Best American plays series, 1949)
Covers American theater's formative period, 1916-1929, with 25 complete plays, biographical and production data, and a survey of the period's drama and dramatists. This volume supplements the two previously published collections: Twenty best plays of the modern American theatre (1929-1939), first series and Best plays of the modern American theatre (1939-1946), second series.